2020
DOI: 10.3390/s20051296
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Crop Growth Parameters Using UAV-Based Hyperspectral Remote Sensing Data

Abstract: Above-ground biomass (AGB) and the leaf area index (LAI) are important indicators for the assessment of crop growth, and are therefore important for agricultural management. Although improvements have been made in the monitoring of crop growth parameters using ground- and satellite-based sensors, the application of these technologies is limited by imaging difficulties, complex data processing, and low spatial resolution. Therefore, this study evaluated the use of hyperspectral indices, red-edge parameters, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 61 publications
3
45
0
1
Order By: Relevance
“…Meanwhile, more spectral information may not be useful in some cases. Tao et al (2020) used hyperspectral sensors to study the correlation between different vegetation indices (VIs) and red-edge parameters and crop biomass. It was found that using too many spectral features as independent variables will lead to overfitting of the model, so it is necessary to use an appropriate number of spectral features that are highly related to biomass.…”
Section: Spectral Sensorsmentioning
confidence: 99%
“…Meanwhile, more spectral information may not be useful in some cases. Tao et al (2020) used hyperspectral sensors to study the correlation between different vegetation indices (VIs) and red-edge parameters and crop biomass. It was found that using too many spectral features as independent variables will lead to overfitting of the model, so it is necessary to use an appropriate number of spectral features that are highly related to biomass.…”
Section: Spectral Sensorsmentioning
confidence: 99%
“…Remote sensing technology makes it possible to monitor crop growth and physiological parameters rapidly and nondestructively in large areas, providing important technical support for non-destructive monitoring of crop growth [34,[36][37][38]. Many achievements have been made in crop growth monitoring by remote sensing, including empirical statistical methods and radiative transfer models [39]. The empirical statistical methods include VI models [40][41][42], principal component regression [43,44], backpropagation (BP) neural network [36], partial least squares regression (PLSR) [45,46], which are widely used for their simplicity and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…At the pre-heading stage, VIs usually shows a strong relationship with crop biomass, so most scholars built the relationships between VIs and AGB to monitor rice growth [34]. For example, Tao H et al used stepwise regression (SWR) and PLSR methods based on VIs, red-edge parameters, and their combinations to accurately estimate AGB and LAI [39]. Devia C A used seven VIs and their combinations to estimate rice biomass in the large area based on Unmanned Aerial Vehicle (UAV) with an average correlation of 0.76 [48].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperspectral remote sensing technology has the unique advantages of high spectral resolution and spectrum unity, representing a revolutionary step in the history of remote sensing technology development [1][2][3]. Based on this 3D spectral data cube, which can acquire both 2D spatial and 1D spectral information, it is possible to detect and identify targets that are difficult to detect and identify with conventional imaging techniques [4][5][6][7][8][9][10]. Spectral imaging data include 2D spatial information and 1D spectral information, whereas imaging detectors are 2D detectors and can only acquire 2D information at a single transient.…”
Section: Introductionmentioning
confidence: 99%